IOT-BASED SOIL PH AND MOISTURE MONITORING TOOL FOR ORNAMENTAL PLANTS - Nujjiya Restu Fauzian; Agus, Agus Ramdhani Nugraha (ADVANCE INFORMATICS RESEARCH JOURNAL, 2025)
Soil plays an important role in human life. In agriculture, the choice of soil type can determine the success rate of farming. Some soil parameters that need to be studied are temperature, moisture and pH, because these three parameters have a very important role in plant fertility. Conduct a literature review to understand existing IoT technologies, available pH sensors, pH level monitoring systems, and related research in ornamental plants. Design the overall system, including the selection of the pH sensor, humidity sensor, and IoT platform to be used. Plants are plants that are nurtured and cared for to benefit or harvested when they reach a certain time. Plants are very useful to fulfill human needs.Soil fertility is the ability of soil to provide nutrients, water and oxygen in a balanced state for plants. Soil reaction indicates the acidity or alkalinity of the soil expressed by the pH value. The purpose of developing this tool may be to assist ornamental plant owners in managing the environmental conditions of their plants more efficiently and accurately. By using IoT-based tools, it is expected to provide convenience in monitoring and controlling environmental factors that affect the growth and health of ornamental plants.